ЭТНОТОПОНИМЛЕРДИ ҮЙРЕНИЎ МӘСЕЛЕСИНЕ - Эназаров, Т.Дж.; Есемуратов, А.Е.; Бердиева, Б.Т. (FAN va JAMIYAT, 2017)
The article describes the problems of studying ethnotoponyms of the Karakalpak language. Names related to the old ideology were replaced by the original names of the area. The authors present their views on the importance and use of toponyms in the methodological aspect. Toponymy of Uzbekistan and Karakalpakstan is rich and the author state their opinions about the collected material.